2007
DOI: 10.3928/00220124-20070301-08
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Clinical Faculty Revisited: The Benefits of Developing Staff Nurses as Clinical Scholars

Abstract: One of the major contributing factors to the nursing shortage in Colorado and nationally is a scarcity of clinical faculty required to prepare new nurses. This article describes an innovative, collaborative project that purposefully prepares staff nurses to assume the role of clinical scholar. Although there are several models that have sought to make clinically expert nurses available as teaching faculty, the breadth and scope of the described project with its multiple partners is unique. In the first year of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…Use of EBP in the health care setting Delunas & Rooda, 2009;Seldomridge, 2004Bonnel et al, 2003Delunas & Rooda, 2009Stahl et al, 2008 Satisfaction (n = 12) Satisfaction of clinical faculty Satisfaction of students. Delunas & Rooda, 2009;Kowalski et al, 2007;Murray, 2007;Warren & Mills, 2009;Bonnel et al, 2003;Seldomridge, 2004Delunas & Rooda, 2009Kowalski et al, 2007;Murray, 2007;Bonnel et al, 2003;Seldomridge, 2004 Recruitment and retention (n = 6) Recruitment Students into the program Faculty into the program Students into workforce Retention of nursing staff and clinical faculty.…”
Section: Discussionmentioning
confidence: 99%
“…Use of EBP in the health care setting Delunas & Rooda, 2009;Seldomridge, 2004Bonnel et al, 2003Delunas & Rooda, 2009Stahl et al, 2008 Satisfaction (n = 12) Satisfaction of clinical faculty Satisfaction of students. Delunas & Rooda, 2009;Kowalski et al, 2007;Murray, 2007;Warren & Mills, 2009;Bonnel et al, 2003;Seldomridge, 2004Delunas & Rooda, 2009Kowalski et al, 2007;Murray, 2007;Bonnel et al, 2003;Seldomridge, 2004 Recruitment and retention (n = 6) Recruitment Students into the program Faculty into the program Students into workforce Retention of nursing staff and clinical faculty.…”
Section: Discussionmentioning
confidence: 99%
“…The Institute of Medicine Report (2009) testified the shortage of health professions faculty is one of the major challenges facing the twenty-first century; so innovative solutions must be sought to meet the objectives of the nursing (Kowalski et al, 2007). This idea of the role of CP was conceived by the nursing management at school of nursing.…”
Section: Q1 Why Was There the Need For Clinical Preceptors In The Unmentioning
confidence: 99%
“…[13] Staff nurses' ability to facilitate clinical learning, role transition, and professional socialization of students is documented in research; [14,15] however, simply because a nurse is an expert clinician does not mean that he or she is an expert preceptor. In fact, the preceptor role has been described as one that is full of role ambiguity, overload, and conflict.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[28] Preceptors themselves have stressed the need for clearer role expectations, guidance, and support; [17,29] however, preceptors have reported that they feel ill-prepared to assume the role. [13,30,31] Kowalski et al [15] suggest that a lack of preparation is a reason for burnout and dissatisfaction with nurses working as preceptors. There is consensus in the literature that preceptors need some type of preparation.…”
Section: Literature Reviewmentioning
confidence: 99%